2013
DOI: 10.29087/2013.5.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Scholar-Librarian Collaboration in the Publication of Scholarly Materials

Abstract: Recent developments in scholarly publication and the new directions being pursued in both humanities departments and libraries in the production of digital content provide opportunity for scholars and libraries to explore new models for working together to produce and disseminate scholarly materials. We offer as a first step toward a model for publication the case of Opuscula: Short Texts of the Middle Ages and Renaissance (OSTMAR), a hybrid form of publication that leverages the university library infrastruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In terms of academic preparation, the participants confirmed that LIS Master's degree training adequately prepared them to read and understand research but it did not prepare them to conduct research. In another recent study, Harkema and Nelson (2013) discussed the role of librarians in scholarly environment, as the librarians make the published content findable and accessible to the researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of academic preparation, the participants confirmed that LIS Master's degree training adequately prepared them to read and understand research but it did not prepare them to conduct research. In another recent study, Harkema and Nelson (2013) discussed the role of librarians in scholarly environment, as the librarians make the published content findable and accessible to the researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…National or consortial collaboration could be a way forward in tackling these challenges as this would enable libraries to act as a collective instead of fending for themselves (Barnes, 1997; Burnhill & Otty, 2015). Other studies point toward closer collaboration between libraries and individual scholars, underlining the importance of addressing the issue of preservation as early as possible in the publishing process (Harkema & Nelson, 2013; Moulaison & Million, 2015). Establishing preservation as an integral part of the publishing process would have the benefit of coordinating efforts and creating a sense of shared responsibility to act more effectively.…”
Section: Literature Reviewmentioning
confidence: 99%